2023
DOI: 10.1093/jpp/rgac086
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional benefits, ethnomedicinal uses, phytochemistry, pharmacological properties and toxicity of Spondias mombin Linn: a comprehensive review

Abstract: Objectives Spondias mombin is traditionally used as an herbal medicine for several human diseases and ailments in the tropical regions across the globe including the African countries. This study aimed to provide comprehensive information on nutritional benefits, ethnomedicinal uses, phytochemical constituents, pharmacological properties and toxicology study of S. mombin. Information was gathered from documented literatures in scientific database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…It was observed that some of the IEWFs have diverse alternative uses other than the edibility of the fruits. Olalekun et al (2003) documented that S. mombin fruits have various uses, its fruits are usually consumed fresh or processed and are generally accepted for their unique sweet-sour taste. The same fruits are used to treat angina, stomach ulcer, vaginal and uterine disorder; the squeezed fruit juice is taken as heart tonic in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that some of the IEWFs have diverse alternative uses other than the edibility of the fruits. Olalekun et al (2003) documented that S. mombin fruits have various uses, its fruits are usually consumed fresh or processed and are generally accepted for their unique sweet-sour taste. The same fruits are used to treat angina, stomach ulcer, vaginal and uterine disorder; the squeezed fruit juice is taken as heart tonic in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…From 2019, there was a substantial increase in publication numbers followed by 2020 and 2021. The areas of knowledge are mainly distributed among biotechnology applied microbiology (33), pharmacology/pharmacy (32), food science and technology (21), and polymer science (17). Some applications are focused on the preparation of functional food and beverages, extraction and isolating active substances such as flavonoids and other phenolic compounds, as well as pharmaceutical and cosmetic formulations.…”
Section: Nutritional and Mineral Compositionmentioning
confidence: 99%
“…However, they do not bring together, in the same work, information about S. tuberosa and S. mombin, unlike this review, which brings together information about academic research and patents relating to the two fruits. Also, a bibliometric analysis of articles published in the last 20 years is provided herein; these characteristics differ this review from others that are already published [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…7,[9][10][11] It is a medicinal plant that has wide acceptability and proven to exert certain beneficial health activities which include antiepileptic, antidementia, antipsychotic, anticancer, cytotoxic, anthelmintic, antiviral, and anxiolytic pharmacological activities. [12][13][14][15]…”
Section: Introductionmentioning
confidence: 99%